Composition, microstructure, and friction behavior of PIRAC chromium carbide coatings prepared on Q235 and T/P 24. Issue 2 (28th September 2017) - Wu, Siyuan; Ma, Shaojun; Wu, Shoujun; Zhang, Guoyun; Dong, Ning
Abstract: Chromium carbide coatings are prepared at 1173K (900°C) by powder immersion reaction‐assisted coating (PIRAC) on low carbon of steel Q235 and T/P 24, respectively. After 2 hours of the PIRAC treatment, the detected phases of the coating formed on the 2 substrates are different. After 4 hours of PIRAC treatment, Cr23 C6 is the only detected carbide for both substrates. The morphologies of the Cr23 C6 coating formed on the 2 substrates are different. The Cr23 C6 coating prepared on Q235 has higher hardness and better sliding wear resistance against alumina ball specimens than that prepared on T/P 24. Formation mechanism of the PIRAC chromium carbide coatings is proposed and then difference of the produced coating is discussed.